KEEFEKTIFAN MEDIA FLIP CHART UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN DI RA SALSABILA 7 BAKALAN - Harni Sarinda Magibfa; Umi Faizah (QURROTI, 2021)
The background of this research problem is that students at RA Salsabila 7 Bakalan are less stimulated by the potential for early reading. In addition, the use of teaching aids is less varied, so that children are less interested and motivated in early reading skills. Therefore, it is necessary to conduct a study that aims to determine the effectiveness of flip chart media to improve early reading skills in children aged 5-6 years at RA Salsabila 7 Bakalan. The purpose of this study was to determine the differences in early reading skills between children who were taught using flip chart media and those who were not taught using flip chart media, and to find out how effective flip chart media is to improve early reading skills in children aged 5-6 years at RA Salsabila 7 Future Pendowoharjo Sewon Bantul. Data collection techniques in this study were observation, tests, and documents. This type of research is quantitative research with a quasi-experimental approach. The subjects used were students of RA Salsabila 7, aged 5-6 years, totaling 12 students. The results of this study indicate that: 1) There is a difference in initial reading ability between students who are taught using Flip Chart media and those who are not taught using Flip Chart media with the results of a significance level (p = 0.003) <0.05. 2) The use of flip chart media is proven to be effective in improving early reading skills with evidence that the results of increasing student learning in the experimental group are higher by 10.17 or 56.5% and the control group by 3.67 or 33.36%.